2010
DOI: 10.1177/0969776409357362
|View full text |Cite
|
Sign up to set email alerts
|

Migration and uneven development within an enlarged European Union: Fathering, gender divisions and male migrant domestic services

Abstract: Drawing mainly on qualitative evidence gathered from interviews with migrant handymen and with labour-using households in the UK, this paper analyses how this migration typifies economic and social divisions within Europe and embodies conflicting tensions between economic and social policies at an interpersonal level. By supplying household services, migrant handymen enable labour-using households to alleviate time pressures and conflicts in time priorities arising from tensions between economic expectations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Much early research into the phenomenon of the A8 expansion concentrated on examining the demographics of those migrating, the types of jobs that they were moving into, and their qualifications and earnings as compared to native workers. This research found that despite their relatively high levels of formal education (Author, 2009;Drinkwater et al, 2006;Williams, 2009), the majority of recent migrants to the UK were found to have taken low skilled jobs (Datta, 2009;Markova et al, 2013;Perrons et al, 2010;Stenning and Dawley, 2009), often on a temporary or agency basis (Author, 2016). In contrast to previous groups of migrants, those from the A8 nations have moved into both rural and urban regions rather than just the latter, and also into areas with lower levels of unemployment (Green, 2009).…”
Section: Migration To the Ukmentioning
confidence: 99%
“…Much early research into the phenomenon of the A8 expansion concentrated on examining the demographics of those migrating, the types of jobs that they were moving into, and their qualifications and earnings as compared to native workers. This research found that despite their relatively high levels of formal education (Author, 2009;Drinkwater et al, 2006;Williams, 2009), the majority of recent migrants to the UK were found to have taken low skilled jobs (Datta, 2009;Markova et al, 2013;Perrons et al, 2010;Stenning and Dawley, 2009), often on a temporary or agency basis (Author, 2016). In contrast to previous groups of migrants, those from the A8 nations have moved into both rural and urban regions rather than just the latter, and also into areas with lower levels of unemployment (Green, 2009).…”
Section: Migration To the Ukmentioning
confidence: 99%
“…Another form of internationalization and liberalization was also increasingly significant following the 2004 enlargement of the EU, although its roots went much further back -that of international labour migration from Eastern Europe to the 'old' EU member states (see Mingione, 2009;Stenning and Dawley, 2009;Wills et al, 2009;Perrons et al, 2010). Creating emerging forms of relational, transEuropean labour markets, labour migration anchored relatively low-cost labour in the labour markets of the UK, Ireland and elsewhere into wider transnational networks of income flows from West to East.…”
Section: The Changing Economic Geographies and Urban And Regional Tramentioning
confidence: 99%
“…Having been helped by his relatives in Sweden to establish a private company registered in Poland, Jakub initially worked in Sweden as a self-employed construction worker. As a livelihood strategy, it was a very common arrangement among many male migrants from Poland, Romania and other new EU member states, who performed various construction jobs for the private households in the wealthier EU countries (Perrons et al, 2010;Faist, 2014). As a self-employed worker, Jakub did not have any rights to social protection or welfare benefits from the Swedish welfare state.…”
Section: Methodsmentioning
confidence: 99%
“…The propensity to move in search for a job remained stable even after the 2008 economic crisis, with more prolonged stays and greater permanency than in the first few years after the enlargement of the EU (Ryan et al, 2009;Slany and Pustulka, 2016). Several researches attributed this enduring mobility to the unprecedented differences in the living standards within the EU since its enlargement (Perrons et al, 2010;Black et al, 2010). For instance, Dølvik (2013) noted that the nominal wages in the new EU member states ranged from one-tenth to one-seventh of those in the rest of the EU, while the living standards were on average 45 per cent of those in Western Europe prior to accession.…”
Section: New Geographies Of Mobility In Europementioning
confidence: 99%
See 1 more Smart Citation